Kendala Mengimplementasikan Jurnal Reflektif sebagai Bentuk Profesionalisme Guru MI - Nasyariah Siregar; Fia Alifah Putri; Vioni Saputri; Sri Ramdayeni Sakunti (Departement of Mathematics Education, 2023)
Reflective journal as a record in analyzing process, performance, and follow-up through contemplation of things that the teacher encounters. In learning, reflective journals are used as a medium to improve the learning process. This reflection journal study is expected to be able to open up space for knowledge in the world of teacher professionalism. This research also functions as an accurate prototype in viewing the constraints of implementing MI teacher's reflective journals in the learning process. By using a descriptive qualitative research method, it is considered capable of guiding this research. By describing and describing the application of reflective journals as a form of professionalism for Madrasah Ibtidaiyah (MI) teachers. Reflective journal descriptions are obtained through observation, interviews, and data/document analysis. Observation sheets can be used through observation, interviews conducted with research informants, and data collection. The results of the study found three obstacles in implementing reflective journals as a form of MI teacher professionalism, namely: (1) Teachers are accustomed to writing reflective journals after each lesson, (2) Lack of motivation for teachers to routinely apply reflective journal writing in every learning activity, and (3) Dissemination is not evenly distributed to each school, so that only certain schools understand reflective journal writing and the benefits provided.